Analisis Pengelolaan Usaha Koperasi Pemuda Tri Karya Ambon Cabang Lateri - Larwuy, Marthon; Pelamonia, Merryl; Rehatta, Geradin (Jurnal Pendidikan Ekonomi, 2024)
Cooperatives as collective business entities play a crucial role in improving the economic welfare of their members through management of business units, marketing, and finance. This study aims to analyze the management practices of the Tri Karya Youth Cooperative, Lateri Branch, Ambon, as well as to identify challenges faced in the management process. A descriptive qualitative approach was used, employing in-depth interviews and documentation involving cooperative managers and staff. The results show that the management of business units, marketing, and finance has been implemented effectively, yet there are still obstacles such as problematic loans and low member participation. The conclusion highlights the need for enhanced professionalism among management, improvement of internal control systems, and strengthening member involvement in all management aspects. This study provides new insights into cooperative management strategies at the local level and can serve as a reference for other cooperatives facing similar issues. The practical implications include the need for ongoing management training, financial transparency, and a collaborative approach with members to ensure competitiveness and sustainability